UPAYA GURU BIMBINGAN KONSELING DALAM MENINGKATKAN KEDISIPLINAN PESERTA DIDIK DI SMP NEGERI I DUNGKEK SUMENEP - Khotijah, Sitti Khotijah; Eva Solina; NazlahHidayati (Conseils : Jurnal Bimbingan dan Konseling Islam, 2023)
Discivision of discipline for learners is an important point and step in education, especially for counseling / BK guidance teachers. This is due to disciplial enforcement for learners have attachments in building and forming self-characteristics. For that in this study raised themes on teacher efforts and counseling in improving disciplusion of learners in SMP Negeri 1 Dungkek with a focus of the problem at: first, how was the teacher's efforts to counseling in improving the discipline of learners in SMP Negeri 1 Dungkek ?. Second, how do the teacher's efforts to counseling guidance in improving the discipline of learners in SMP Negeri 1 Dungkek?. The research approach used is qualitative research with the type of research is case study. The location of the study at SMP Negeri 1 Dungkek, and the technique of data collection through interviews, observation and documentation. The results showed that. First, the teacher's efforts to counseling in enhancing disciplines of SPM Negeri 1 Dungkek has taken several steps, namely: First guru Counseling Guidance Teacher in improving discipline students in SMP Negeri 1 Dungkek: Higher, Control / Supervision, Concerning, and provides a good example. Secondly, the result of the teacher's counseling effort in improving the discipline of learners in SMP Negeri 1 Dungkek: Creating students are well trained and controlled, and able to control themselves.